Is the coronal plane alignment of the knee (CPAK) classification useful to plan individualized total knee arthroplasty surgery for the Spanish population? A critical analysis of the CPAK classification - O. Pujol; P. Hinarejos; A. Pons; E. Famada; A. Zumel; J. Erquicia; J. Leal-Blanquet (Revista Española de Cirugía Ortopédica y Traumatología)
Introduction: The CPAK classification aims to categorize knee phenotypes. The original study was based on Australian and Belgian population, but significant variation in CPAK distribution exists between different geographic areas. The primary objective is to evaluate knee phenotypes of osteoarthritic Spanish population based on the CPAK system. The secondary objective is to compare the Spanish CPAK distribution with that observed in the original study to analyse if proposing modifications is necessary when applying the classification to our population. Finally, we aim to critically analyse the utility of this classification to plan individualized TKA. Methods: It is a cross-sectional observational study analysing radiological datasets from 121 patients with knee osteoarthritis treated with a Mako assisted TKA in three Spanish institutions. The preoperative lower limb CT-scan was used to measure the MPTA and LDFA of each patient. Then, the aHKA (MPTA − LDFA) and JLO (MPTA + LDFA) were calculated to categorize patients into the nine CPAK phenotypes. Results: The commonest knee phenotypes of osteoarthritic Spanish population were the distal apex JLO CPAK types (74%: II (28%), I (23%) and III (23%)). No patient presented a proximal apex type (VII, VIII and IX). The 30% of the patients had a varus alignment and 26% a valgus. No relevant differences were found between the Spanish CPAK distribution and that observed in the original study. Conclusions: No modifications to the CPAK classification should be necessary for the Spanish population. The CPAK classification can be useful to describe and categorize osteoarthritic patients. However, relevant limitations have been found to the classification, questioning its utility to plan and guide individualized TKA surgery. Resumen: Introducción: La clasificación CPAK tiene como objetivo categorizar los fenotipos de rodilla. El estudio original se basó en población australiana y belga, pero existe una variación significativa en la distribución CPAK entre diferentes áreas geográficas. El objetivo principal es evaluar los fenotipos de rodilla en población española con artrosis utilizando el sistema CPAK. El objetivo secundario es comparar la distribución CPAK española con la observada en el estudio original para analizar si es necesario proponer modificaciones al aplicar la clasificación a nuestra población. Finalmente, se analizará críticamente la utilidad de esta clasificación al planificar una ATR individualizada. Métodos: Estudio observacional transversal que analiza datos radiológicos de 121 pacientes con artrosis de rodilla tratados mediante ATR asistida por Mako en tres instituciones españolas. Se utilizó la tomografía computarizada preoperatoria de la extremidad inferior para medir el MPTA y el LDFA de cada paciente. Posteriormente, se calcularon el aHKA (MPTA-LDFA) y JLO (MPTA+LDFA) para categorizar a los pacientes en los nueve fenotipos CPAK. Resultados: Los fenotipos de rodilla más comunes en la población española con artrosis fueron los tipos CPAK de ápex distal (74%: II (28%), I (23%) y III (23%). Ningún paciente presentó un fenotipo con ápex proximal (VII, VIII y IX). El 30% de los pacientes tenían una alineación en varo y el 26%, en valgo. No se encontraron diferencias relevantes entre la distribución CPAK española y la observada en el estudio original. Conclusiones: No deberían ser necesarias modificaciones a la clasificación CPAK para la población española. La clasificación CPAK puede ser útil para describir y categorizar a los pacientes con artrosis. Sin embargo, se han encontrado limitaciones relevantes en la clasificación, cuestionando su utilidad para planificar y guiar la cirugía de ATR individualizada.